If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(3z + -1) = 6 + -4z Reorder the terms: 6 + -1(-1 + 3z) = 6 + -4z 6 + (-1 * -1 + 3z * -1) = 6 + -4z 6 + (1 + -3z) = 6 + -4z Combine like terms: 6 + 1 = 7 7 + -3z = 6 + -4z Solving 7 + -3z = 6 + -4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4z' to each side of the equation. 7 + -3z + 4z = 6 + -4z + 4z Combine like terms: -3z + 4z = 1z 7 + 1z = 6 + -4z + 4z Combine like terms: -4z + 4z = 0 7 + 1z = 6 + 0 7 + 1z = 6 Add '-7' to each side of the equation. 7 + -7 + 1z = 6 + -7 Combine like terms: 7 + -7 = 0 0 + 1z = 6 + -7 1z = 6 + -7 Combine like terms: 6 + -7 = -1 1z = -1 Divide each side by '1'. z = -1 Simplifying z = -1
| 7x-8(0)=56 | | 6x+10=4x-8 | | r^2-15=-2r | | 9(y-6)=8(y-9) | | -1/2x^2+100x | | 7(0)-8y=56 | | 13x-12=49x+24 | | 24z-48z=.72 | | 5x-14=x-(24+4x) | | w-3/2=5/8 | | -11/2h=4 | | 4(x-4)+6=6x-2(3+x) | | x+(x-12)=58 | | -31/3b=5 | | 14x-8x+9=33 | | 14x-8+9=33 | | (1+3w)(2)= | | 9m+1/4=8/1/2m+2/3 | | 4x-5=4(x+7) | | 18x+12-14x=-24 | | x-0.25+25.00=250.00 | | 7/10m=10 | | 3k=.03+7k | | 2(5-x)=-2-5+x | | 3x=9y-6 | | 20(x+8)=4(40+5x) | | (74+82+x)/3=80 | | 5y+6x=20 | | 6x+8x+12=82 | | 3+0.1(7-x)=1.3x-(0.5x-3.7) | | 74+82+x=80 | | 3+0.1(7-x)=1.3x-(0.5x-3.7)findX |